MICROCONTROLLERS AND AUTOMATIC CONTROL OF VIBRATION MACHINES - M. O. Khalikova (European Science Publishing, 2023)
Microcontrollers allow flexibility to manage a variety of electronic and electrical devices. Some models are so powerful microcontroller that can directly switch the relay. In 1990-1991 there were actually 2-5 digital signal type names PAL and GAL, analog digital converters, classic operational amplifiers.
Keywords: microcontroller, electromagnetic vibration motors, vibration machines, dynamic mode, electric drive, scalar control, nonlinear differential equation.